Socialization of regional regulations regarding waste management to increase awareness of environmental cleanliness for MSMEs - St Salmah Sharon; Yuyun Karystin Meilisa Suade; Cindy Yoel Tanesia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Environmental management has become a major issue for Partner Groups, especially those in the Losari Beach area. Awareness regarding the importance of environmental cleanliness has been established with the existence of regulations that regulate environmental management, especially waste management. However, the socialization related to government programs has not touched business actors in Losari Beach. Therefore, this community service aims to provide socialization of PP No. 4 of 2011 regarding the waste management program as an effort to increase awareness of environmental cleanliness. A clean environment can attract domestic and foreign tourists which will directly have an impact on increasing the income of Micro, Small, and Medium Enterprises (MSMEs). The stages of implementing the activities are the preparation stage and the implementation stage using the socialization method. The result of the service is that the community understands the purpose of the PP Regional Regulation No. 4 of 2011 for MSMEs, one of which is protecting the environment as a tourist attraction. The high number of tourists visiting has an impact on purchasing power, thus Micro, Small, and Medium Enterprises (MSMEs) continue to exist to maintain their business.